中炭素マルテンサイト鋼の焼戻し軟化抵抗に及ぼすSi，Cr，Moの影響 - 高橋, 淳; 寺本, 真也; 久保田, 学 (Transaction of Japan Society of Spring Engineers, 2020)
The addition of alloy elements such as silicon, chromium and molybdenum is effective in the restraint of temper softening in martensitic steels. The martensitic steel containing such alloy elements is known to have excellent resistance to temper softening in low and high temperature tempering treatments. However, the effects of the compound addition and its mechanism have not yet been satisfactorily revealed. In this study, the effect silicon, chromium, and molybdenum on resistance to the temper softening of the medium-carbon martensitic steel was investigated. As a result, it is revealed that the temper softening resistance quantity is maximum at the tempering temperature 773 K in the martensitic steel containing silicon, chromium, and molybdenum; this is because of the miniaturization of cementite (θ) and clustering of (Cr,Mo,Mn) 2C. Moreover, it is revealed to form this cluster at a tempering temperature lower than the temperature at which the alloy carbide usually precipitates (823 K-873 K).